MicroRNAs in non-alcoholic fatty liver disease: Progress and perspectives - Mette Yde Hochreuter; Morten Dall; Jonas T. Treebak; Romain Barrès (Elsevier, 2022)
Background: Non-alcoholic fatty liver disease (NAFLD) is a spectrum of disease ranging from simple hepatic steatosis (NAFL) to non-alcoholic steatohepatitis (NASH) which may progress to cirrhosis and liver cancer. NAFLD is rapidly becoming a global health challenge, and there is a need for improved diagnostic- and prognostic tools and for effective pharmacotherapies to treat NASH. The molecular mechanisms of NAFLD development and progression remain incompletely understood, though ample evidence supports a role of microRNAs (miRNAs) - small non-coding RNAs regulating gene expression - in the progression of metabolic liver disease. Scope of review: In this review, we summarise the currently available liver miRNA profiling studies in people with various stages of NAFLD. We further describe the mechanistic role of three of the most extensively studied miRNA species, miR-34a, miR-122 and miR-21, and highlight selected findings on novel NAFLD-linked miRNAs. We also examine the literature on exosomal microRNAs (exomiRs) as inter-hepatocellular or -organ messengers in NAFLD. Furthermore, we address the status for utilizing circulating NAFLD-associated miRNAs as minimally invasive tools for disease diagnosis, staging and prognosis as well as their potential use as NASH pharmacotherapeutic targets. Finally, we reflect on future directions for research in the miRNA field. Major conclusions: NAFLD is associated with changes in hepatic miRNA expression patterns at early, intermediate and late stages, and specific miRNA species appear to be involved in steatosis development and NAFL progression to NASH and cirrhosis. These miRNAs act either within or between hepatocytes and other liver cell types such as hepatic stellate cells and Kupffer cells or as circulating inter-organ messengers carrying signals between the liver and extra-hepatic metabolic tissues, including the adipose tissues and the cardiovascular system. Among circulating miRNAs linked to NAFLD, miR-34a, miR-122 and miR-192 are the best candidates as biomarkers for NAFLD diagnosis and staging. To date, no miRNA-targeting pharmacotherapy has been approved for the treatment of NASH, and no such therapy is currently under clinical development. Further research should be conducted to translate the contribution of miRNAs in NAFLD into innovative therapeutic strategies.